“We are trying to teach them life things”: Insights from a university-schools collaborative engagement project to enhance STEM teaching capacities at secondary schools - Du Plooy, B.; Du Preez, K. (South African Journal of Higher Education, 2025)
The state of school education in South Africa, especially in Science, Technology, Engineering and Mathematics (STEM) subjects, is commonly acknowledged as a great concern, to the extent that it has been called a national crisis (Grayson, 2009:7). This causes a long-term pipeline problem, or “articulation gap” (Case, Marshall & Grayson. 2013:1), in the tertiary education sector and in STEM-related job markets. There are consistently declining numbers of learners who choose subjects like Mathematics and Physical Sciences at school, which removes them from the pool of learners who could potentially qualify in these fields at post-school and tertiary level and who are therefore also lost to STEM careers. This article reports on a small multistakeholder university engagement project conducted between 2015 and 2020 at nine schools in one province of SA by the Engineering Faculty of a local university. A variety of STEM-related interventions aimed to upgrade facilities and equipment, supply resources necessary for the training of learners in the sciences and technologies and raise awareness of engineering careers among learners and teachers. This qualitative post-implementation research project used interviews to gather information regarding the perceptions of project collaborators (school educators, principals and university staff) about the university’s interventions to enhance STEM teaching at participating secondary schools. The findings were collated into ten themes that speak of benefits for learners and educators, improvements for schools and the university’s role regarding social responsibility. The knowledge gained through these interventions can be extended to and applied by other STEM training sectors and programmes, both public and private.